Le contexte culturel et linguistique de la langue kurde Cultural and linguistic context of the Kurdish language - Bakhtyar Hussen Ahmad (Zanco Journal of Humanity Sciences)
This research aims to focus on the context and progression of the Kurdish language of today while comparing it with the French language. We try here to present the history of the Kurdish language as well as its progression, its rebirth for several decades. This study also tends to explain how the Kurdish oral, through centuries, has been made up of several dialects and according to the political, sociological and urban opportunities, has turned into a complete language used as the oral that 'written. Each dialect was the outcome of a set of a way of life in a specific region and in a specific period. These dialects were analyzed according to three factors; their understandings, their geographical areas and their expansions. But, according to Kurdish linguists, it is difficult to identify the boundaries between Kurdish dialects. We chose the Sorani dialect (Central Kurdish) as a basis for our study because it was built after a long history and thanks to numerous linguistic, literary and sociological contributions. The use of Sorani as a language of education and media has greatly enriched the Kurdish language. Therefore, the task of defining the boundaries between the dialect and the Kurdish language remains difficult because language is the product of a social agreement on which a group of individuals have agreed.